2019
DOI: 10.3390/nano9121654
|View full text |Cite
|
Sign up to set email alerts
|

Facile One-Step Synthesis and Enhanced Optical Nonlinearity of Graphene-γMnS

Abstract: Graphene-γMnS were prepared by facile one-step hydrothermal method. Structures and properties of samples were explored by characterization, and nonlinear optical (NLO) enhancement of nanocomposites (NCs) was fully studied. Nanoparticles and NCs were tested at 532 nm by a Z-scan technique. With γMnS attached in G layers, NLO susceptibility of graphene-γMnS was greatly improved under single-pulse laser irradiation compared with G and γMnS. The nonlinearity enhanced was attributed to local field effect and charge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…In our previous study, NLO response of αMnS/rGO and γMnS/rGO was investigated. And results showed that nonlinearity of graphene composites was enhanced and the reason for NLO enhancement was surface defects and synergistic effect, including local field theory and charge transfer [18,23]. In this study, NLO absorption and refraction of αMnS with different size and γMnS were measured by Z-scan technique using single Gaussian beam.…”
Section: Nlo Property Of Nanoparticlesmentioning
confidence: 85%
See 4 more Smart Citations
“…In our previous study, NLO response of αMnS/rGO and γMnS/rGO was investigated. And results showed that nonlinearity of graphene composites was enhanced and the reason for NLO enhancement was surface defects and synergistic effect, including local field theory and charge transfer [18,23]. In this study, NLO absorption and refraction of αMnS with different size and γMnS were measured by Z-scan technique using single Gaussian beam.…”
Section: Nlo Property Of Nanoparticlesmentioning
confidence: 85%
“…αMnS nanoparticles obtained after treatment [18]. The volume of nanoparticles decreased as the synthesis time increased and size range was 40 nm to 200 nm [23]. This might be due to high temperature and high pressure in stainless-steel reactor.…”
Section: Structure and Morphology Characterizationmentioning
confidence: 96%
See 3 more Smart Citations